Impact of Associated Infections on the Clinical Course and Risk-Stratification Profile of Pulmonary Embolism: Comparative Analysis Using PESI, Wells, Padua, and IMPROVE Scores - Daniela Nicoleta Crisan; Raluca Dumache; Talida Georgiana Cut; Alexandra Herlo; Marius Florentin Popa; Lucian-Flavius Herlo; Nina Ivanovic; Andreea Nelson Twakor; Gabriela-Florentina Țapoș; Adelina Raluca Marinescu (Diagnostics, 2026)
Background: Pulmonary embolism (PE) remains a major cause of cardiovascular morbidity and mortality, and associated infections may modify its clinical course. This study evaluated the impact of viral infections on pulmonary embolism severity, mortality, and the performance of established risk scores. Methods: This retrospective observational study included 729 patients with confirmed PE admitted between January 2020 and December 2025. Patients were grouped according to the presence of associated infections. We analysed clinical data, comorbidities, thrombus localization, laboratory parameters, infection type, treatment, mortality, and Pulmonary Embolism Severity Index (PESI), Wells, Padua, and International Medical Prevention Registry on Venous Thromboembolism (IMPROVE) scores. We performed between-group comparisons, logistic regression, and ROC curve analyses. Results: Patients with associated infections had higher crude mortality than those without infections (27.7% vs. 18.4%, p = 0.006). They also showed higher PESI and IMPROVE scores for venous thromboembolism (VTE), increased white blood cell (WBC) count, markedly elevated D-dimers, longer prothrombin time, and different thrombus localization. Viral infection category was independently associated with mortality, with the IMPROVE score showing the highest ROC discrimination among evaluated scores. Conclusions: Associated infections define a higher-risk PE phenotype. Risk stratification should integrate infection status, laboratory markers, and conventional PE/VTE scores.